Working memory retrieval pointers for accessible long-term memory representations ... - Todorova, Lara; Gunseli, Eren (OSF Registries, 2024)
Rapid and frequent information exchange between working memory (WM) and long term memory (LTM) is crucial for successfully handling complex daily tasks that exceed the limited capacity of WM. The “pointers” framework explains such rapid exchange via retrieval cues stored in WM that provide easy access to LTM representations. Using EEG, we will investigate whether spatial pointers in WM could serve as retrieval cues for objects in LTM that are expected to be relevant soon. Participants will be presented with two previously studied objects, one of the items will be attended, and another – unattended. Crucially we will ask participants to hold both items in mind to ensure they are not dropped from memory. We hypothesize that the EEG signal will contain information about the location and object identity of an attended item while the location but not the object identity for the unattended item. We will use well-established markers for object storage in WM (contra-lateral delay activity, CDA) and object location ...